FORMALIZATION OF THE ACCOUNTING VALUABLE MEMES METHOD FOR THE PORTFOLIO OF ORGANIZATION DEVELOPMENT AND INFORMATION COMPUTER TOOLS FOR ITS IMPLEMENTATION - Serhii D. Bushuiev; Valentyna M. Molokanova (Інформаційні технології і засоби навчання, 2017)
The current state of project management has been steadily demonstrating a trend toward increasing the role of flexible "soft" management practices. A method for preparing solutions for the formation of a value-oriented portfolio based on a comparison of the level of internal organizational values is proposed. The method formalizes the methodological foundations of value-oriented portfolio management in the development of organizations in the form of approaches, basic terms and technological methods with ICT using, which makes it possible to use them as an integral knowledge system for creating an automated system for managing portfolios of organizations. The result of the study is the deepening of the theoretical provisions for managing the development of organizations through the implementation of a value-oriented portfolio of projects, which allowed formalize the method of recording value memes in the development portfolios of organizations, to disclose its logic, essence, objective basis and rules.